Impact of Counseling on Knowledge, Feelings and Actions of Over-Indebted Borrowers in Tajikistan - World Bank Group (World Bank, Washington, DC, 2016)
A growing body of empirical work suggests that personalized, just-in-time consultation about financial decision-making, with an emphasis on goal-setting, may be more effective to bring about improvements in financial consumer behavior than generalized, classroom-style education. With this in mind, IFC piloted campaigns to provide free, neutral, confidential financial counseling services to consumers in Tajikistan in early 2016, attracting about five thousand participants. Consultations included identification of personal financial goals, mapping out of major upcoming expenses and income, identification of risks, and opportunities for savings. In order to assess the impact of counseling campaigns on consumers’ knowledge about their financial standing, feelings of readiness and capability to make good decisions, and actions to better balance income and expenses, maintain a household budget, IFC carried out an impact assessment of participants and control groups from two of the cities, Kurgantiube and Kulyab, at 0-, 3- and 6-months from the time of the counseling campaigns. The results provide valuable insights into the ways that counseling can drive financial consumers to change their behavior.